IMPLEMENTASI GOOGLE EARTH SEBAGAI MEDIA PEMBELAJARAN KONTEKSTUAL PADA MATA PELAJARAN GEOGRAFI - Tue, Febriyani; Lukum, Astin (LP2M IAIN Sultan Amai Gorontalo, 2025)
Effective geography education requires instructional media capable of visualizing spatial phenomena in a realistic and interactive manner. Google Earth, a digital mapping application based on satellite imagery and geospatial data, offers an innovative approach to address this need. This study aims to examineimplementation and advantages of Google Earth as a contextual learning medium in geography education through a systematic literature review. The analysis reveals that Google Earth significantly enhances students’ comprehension of key geographical concepts, including absolute and relative location, spatial distribution, spatial interaction, and regional dynamics, through 3D visualizations and geospatial data exploration. Furthermore, its integration supports project-based and inquiry-based learning models aligned with the Merdeka Curriculum. However, several challenges hinder its implementation, such as limited technological infrastructure, low digital literacy among educators and learners, and various technical issues. To fully leverage the potential of Google Earth in geography instruction, strategic implementation planning, teacher training, and institutional support are essential.